2014
DOI: 10.1016/j.clnu.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary thylakoids suppress blood glucose and modulate appetite-regulating hormones in pigs exposed to oral glucose tolerance test

Abstract: Dietary thylakoids may be a novel agent in reducing the glycaemic responses to high carbohydrate and high glycaemic index foods. Thylakoids may in the future be promising for treatment and prevention of diabetes, overweight and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…Delayed fat digestion increases the production of the satiety hormones cholecystokinin [9],[10] and glucagon-like peptide-1 (GLP-1) [11] as has been demonstrated in human trials. Additionally, in humans [9] and pigs [12] ingestion of the extract has been shown to suppress the hunger hormone ghrelin. Among the gut hormones involved in appetite regulation GLP-1 in particular has been associated with the regulation of reward induced eating behavior [13].…”
Section: Introductionmentioning
confidence: 99%
“…Delayed fat digestion increases the production of the satiety hormones cholecystokinin [9],[10] and glucagon-like peptide-1 (GLP-1) [11] as has been demonstrated in human trials. Additionally, in humans [9] and pigs [12] ingestion of the extract has been shown to suppress the hunger hormone ghrelin. Among the gut hormones involved in appetite regulation GLP-1 in particular has been associated with the regulation of reward induced eating behavior [13].…”
Section: Introductionmentioning
confidence: 99%
“…98 Following a four week high fat diet, thylakoids fed to pigs increased plasma CCK concentrations over a period of 6 hours, whereas ghrelin concentrations were reduced in the two to four hour period compared to a control condition without thylakoid administration. 101 Similarly, in pigs fed a high-fat meal with or without thylakoids, lipase-colipase activity and portal blood CCK concentrations increased; however insulin levels were lower with thylakoid supplementation. 102 In animal studies, in periods ranging from 13 to 100 days, reductions in body weight and body fat have been demonstrated.…”
Section: Animal Studiesmentioning
confidence: 96%
“…113 The increase in CCK concentrations has been consistent in the human 16,103 as well as the animal studies that measured the effect of thylakoids on CCK. 95,100,101 Cholecystokinin has been shown to reduce food intake in both human and animal species; but, the inhibitory effect is generally observed relatively shortly after food ingestion and is of a brief duration. 45 Thus, CCK has been shown to be effective in meal termination which reflects satiation rather than satiety.…”
Section: Human Studiesmentioning
confidence: 99%
“…We found that these effects are connected to an altered secretion of appetite regulating hormones, including ghrelin, cholecystokinin (CCK) and glucagon-like peptide-1 (GLP-1), in rodents, pigs and humans (Köhnke, Lindbo et al, 2009;Montelius, Osman et al, 2013;Montelius, Szwiec et al, 2013;Montelius et al, 2014). Based on these findings of suppressed hedonic hunger and increased levels of GLP-1, we were interested to deepen our knowledge of these effects on overweight middle-aged women in a similar group of participants but in a non-laboratory setting.…”
Section: Introductionmentioning
confidence: 99%